Pemanfaatan Kanal Youtube Pada Pelajaran Aqidah ahlaq Di MI Muawanul Islam Uteran - Hirzulloh, Muhammad Faiq (PKBM DAARUL AHKAAM, 2024)
One of the strategic measures to improve the quality of education involves innovation in pedagogical media. Based on findings from scientific investigations and observations, the subject of aqidah ahlaq is characterized by a degree of monotony, mainly due to its delivery through the traditional lecture method. Aqidah ahlaq includes historical content, thus requiring the involvement of a proficient educator to effectively explain the related material. The purpose of this study is to examine the factors that play a role in enhancing media innovation in aqidah and akhlak learning that has not been fully utilized. Using a field research approach, this study applied qualitative research methodology. The results showed that prior to the introduction of YouTube-based learning media, students' understanding of the aqidah ahlaq material did not meet the expected standards, especially in terms of the minimum compliance criteria that had been set for the subject. Analysis of oral and written assessments showed that only 20% of the 14 participating students demonstrated a satisfactory understanding of the material, while the remaining 80% fell short of the minimum compliance benchmark for aqidah ahlaq learning. After being introduced to the innovative learning media, there was a significant increase in the students' level of understanding.